Novel 3D flower like ZnO/MnV2O6 heterojunction as an efficient adsorbent for the removal of imidacloprid and photocatalyst for degradation of organic dyes in waste water. (1st June 2021) - Kaushal, Sandeep; Kurichh, Parul; Singh, Prit Pal
Abstract: In this investigation, a novel 3D flower like ZnO/MnV2 O6 heterojunction was successfully constructed via facile hydrothermal method, and employed to remove most consumable imidacloprid pesticide and photocatalytic degradation of methylene blue (MB) and methyl orange (MO) dyes in aqueous system. The photocatalytic activities of the heterojunction samples with different dosage were estimated by UV–vis spectroscopy. Nearly, 95.2% of MB and 91.8% of MO dye was decomposed in 60 and 90 min, respectively. The 3D flower like ZnO/MnV2 O6 heterojunction demonstrated 99% adsorption for imidacloprid in 200 min. The effect of diverse factors like pH, contact time and adsorbent dosage on adsorption was investigated. The highest removal efficiency was observed at pH 4 with 0.03 g of adsorbent. The kinetic data was fitted into pseudo first and second order, and intraparticle diffusion kinetics models. It was observed that the data for adsorption of imidacloprid on ZnO/MnV2 O6 heterojunction fits better into pseudo second order kinetic model. The adsorption isotherms fit well into Langmuir adsorption isotherm model than Freundlich and Temkin models. The maximum adsorption capacity of S-I (0.01 g), S-II (0.02 g), S-III (0.03 g) & S-IV (0.05 g) samples was observed as 81.3, 89.3, 128.2 and 147.1 mg g −1, respectively.